Pluralisme dan Integrasi Agama dalam Kebhinekaan dan Keberagaman Indonesia - Fakhiratunnisa, Safira Aura; Arista, Virandra Adhe; Widopuspito, Adena; Ningrum, Tika Kusuma; Firdaus, Arista Aulia (TSAQOFAH, 2022)
Relationships between religions open every gate that forms a unique relationship. But it should be borne in mind that throughout the history of religion, religion has had a "double face" which resulted in its character and character participating in deciding the model of relations formed between religions. Therefore, religious diversity must be maintained in the bonds that form a relationship of inclusiveness, brotherhood and togetherness among its adherents. This research is library research and uses data analysis identification. The steps in analyzing are formulating problems, conducting library research, collecting data, processing data, presenting data, and compiling reports on research results. From this study it was found that 1) the factors that influence the relationship between religious communities, namely religious factors, political factors, social conditions factors, cultural factors, family and kinship factors, government factors, leadership factors and globalization factors, 2) concrete efforts are needed to change the attitudes and religious knowledge of the Indonesian people which were originally exclusive to attitudes and have a pluralist view of diversity knowledge, 3) Maintain religious diversity through moral ties to realize and promote inclusiveness, brotherhood and togetherness among its adherents.